Extreme typhoon events trigger long-lasting power outages and require demand-side solutions to enhance energy resiliency - Yanxue Li; Fu Xiao; Xiaoyi Zhang; Weijun Gao; Yingjun Ruan; Nan Zhou; Daniel M. Kammen (Communications Earth & Environment, 2025)
Abstract As climate change intensifies, the adverse impacts of extreme weather events on energy supply systems will increase. Here, we collected energy grid utility datasets to illustrate causes and recovery processes of extended power outages induced by typhoon events in Japan. We also assessed the performance of demand-side solutions to enhance home energy resilience using household load profiles. We show that power outages present similar recovery curves, with full restoration times highly dependent on maximum wind velocities and affected regions. Ensuring a 24-hour self-energy supply is essential to mitigate outage impacts. Further, our results highlight the importance of off-grid energy storage or production in sustaining critical household energy loads under extended outage conditions. Building electrification scenarios challenges meeting increased demand under power outages. Building electrification and resiliency should be designed in tandem to improve energy security. Findings shed light on the effectiveness of demand-side solutions in enhancing Japan’s home energy resilience.